Animal Welfare in Air Transport - Popović, Boris; Topić Popović, Natalija; Hoti, Nikica (Promet - Traffic&Transportation, 2012)
Animal welfare is becoming an evermore-important factorfor air carriers from the economical viewpoint, due to its importantimpact on the carrier public image. High standard care hasto be taken of animals during transport in order to satisfy an importantsegment of airline customers, either the Business/Firstclass passengers travelling with pets, or influential shippers ofracing horses, dogs, Zoo species etc.Air transp011 of animals, disregarding other advantages,may pose a threat to their health and welfare being a significantmultifactorial stressor. Along with cardiovascular, endocrineand metabolic abe1mtions, it affects the immune response ofan animal and increases susceptibility to infection. Therefore,strict conditions for air transport of eve1y animal species havebeen imposed. Transport of only healthy animals is approved,as it is necessG/y to prevent the spread of disease during transportand to provide satisfactOJy environment for animals to betransported.